Back Cover: Tin – an unlikely ally for silicon field effect transistors? (Phys. Status Solidi RRL 4/2014). Issue 4 (April 2014) - Hussain, Aftab M.; Fahad, Hossain M.; Singh, Nirpendra; Sevilla, Galo A. Torres; Schwingenschlögl, Udo; Hussain, Muhammad M.
<x xml:space="preserve">Abstract</x> A low‐cost simple thin film deposition of tin (Sn), followed by thermal annealing based alloying of it into the silicon channel, leads to an enhancement of the performance of silicon‐based CMOS devices. Modelling based on density functional theory (DFT) shows that Sn incorporation may lower the band gap of the silicon channel, while the experimental multi‐gate field effect transistor devices show performance enhancement. Additionally, the device performance analysis indicates its promising usage in low standby power applications for ultra‐mobile computation. The study by Aftab M. Hussain et al. (pp. 332–335) opens up further exploration opportunity for group IV(a) (in the periodic table) based materials for channel engineering in semiconductor device technology. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>